Environmental Biotechnology - Wang, Lawrence K.; Wang, Lawrence K.; Ivanov, Volodymyr.; Ivanov, Volodymyr.; Tay, Joo-Hwa.; Tay, Joo-Hwa.; Hung, Yung-Tse.; Hung, Yung-Tse. (Handbook of Environmental Engineering, 2010)
Volume 10: Environmental Biotechnology in the Handbook of Environmental Engineering series presents the theories and principles of various environmental biotechnologies. This outstanding collection of science information is designed as a basic Environmental Biotechnology textbook as well as a reference book for scientists, researchers, educators, and engineers. The book’s expert panel of authors provides an introduction at a wide range of topics, including sanitary microbiology, microbial systematics, ecology, microbial metabolism, life support systems, solid-state processes and reactors, value-added biotechnology products, anaerobic processes, membrane bioreactors, space life support systems, biospherics, natural environmental systems, aerobic and anoxic biotechnologies, sequencing batch reactors, and flotation biological systems. Volume 10: Environmental Biotechnology and its sister book – Volume 11: Environmental Bioengineering – are indispensable as both basic biotechnology textbooks and comprehensive reference books for all environmentalists. Another gold-standard addition to The Humana Press series, Volume 10: Environmental Biotechnology gives readers a cutting-edge illustration of the theories and principles of biotechnologies, systems, processes, and methodologies. Coverage of basic and advanced environmental biotechnologies, systems, methodologies, and processes. Emphasis on detailed descriptions, introductions, theories, principles, classifications, and mechanisms of microbiology, ecology, life support systems, and biological processes. Reference of practical use to scientists, researchers, educators and engineers. Contents Environmental biotechnology, microbiology, microbial systematics, ecology, metabolism, life support systems, solid-state processes and reactors, value-added biotechnology products, anaerobic suspended biological processes, membrane bioreactors, closed ecological systems, space life support systems, biospherics, natural environmental biotechnologies, aerobic processes, anoxic processes, suspended-growth processed, attached-growth processes, and flotation biological systems.